1996
DOI: 10.1002/(sici)1099-1166(199607)11:7<621::aid-gps359>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Performance of chronic schizophrenic patients on cognitive neuropsychological measures sensitive to dementia

Abstract: Although many chronic schizophrenic patients manifest substantial global cognitive impairment, it is not clear as to whether this impairment should be characterized as dementia. Since many degenerative dementias have a characteristic signature of cognitive impairment and a specific pattern of cognitive decline, examination of schizophrenic patients on these measures can provide information about the qualitative similarity of their cognitive impairment to these other conditions. Three hundred and two chronicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Moreover, the age-related increase in P300 latency in the patients with schizophrenia was significantly greater than in age-comparable controls. The findings from this study by O'Donnell et al (1995) are consistent with the findings from the present study and several previous studies reviewed above (Bilder et al, 1992;Harvey et al, 1995aHarvey et al, , 1995bHarvey et al, , 1996Waddington & Youseff, 1996) that suggest a neurodegenerative process in schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the age-related increase in P300 latency in the patients with schizophrenia was significantly greater than in age-comparable controls. The findings from this study by O'Donnell et al (1995) are consistent with the findings from the present study and several previous studies reviewed above (Bilder et al, 1992;Harvey et al, 1995aHarvey et al, , 1995bHarvey et al, , 1996Waddington & Youseff, 1996) that suggest a neurodegenerative process in schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
“…Bilder et al (1992) used intelligence test profiles to estimate the difference between premorbid and current cognitive functioning in patients with schizophrenia and found that deterioration may follow the onset of psychosis in subgroups of patients. Harvey et al (1995aHarvey et al ( , 1995bHarvey et al ( , 1996 also found significant age-related decline on gross cognitive screening measures in large samples of chronically institutionalized older patients with schizophrenia, suggesting a possible neurodegenerative process. Waddington and Youseff (1996) also found progressive cognitive decline over a 10-year follow-up in chronic inpatients with schizophrenia.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is not clear if the lower Mini-Mental State scores in geriatric patients with poverty of speech were due to schizophrenia or some type of additional condition that induced dementia. Our previous research on cognitively impaired geriatric schizophrenic inpatients has indicated that the pattern of cognitive impairment (22) and postmortem neuropathology (24,25) is different from that seen in degenerative dementing conditions such as Alzheimer's disease. Our most recent research (26) has suggested that even when additional neuropathological causes of dementia are examined postmortem (e.g., vascular dementia, Lewy body dementia, Creutzfeldt-Jakob syndrome), over 75% of cognitively impaired schizophrenic patients have no identifiable neuropathology to explain their cognitive status, which suggests that this cognitive impairment may be an intrinsic feature of a large number of patients with chronically unremitting schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In two different studies of the same sample of patients, Harvey et al (1995) found that, as a group, there was no decline in MMSE scores over a two-year follow-up of 50 elderly patients with schizophrenia. Using a cognitive battery sensitive to the typical cognitive de®cits in AD, Harvey et al (1996) found no signi®cant change over a one-year follow-up period. In contrast, previous studies of patients with AD have revealed statistically signi®cant cognitive declines during the same one-year time frame (Welsh et al, 1991).…”
Section: The Course Of Cognitive and Functional Deficits In Late Lifementioning
confidence: 99%